Faith in foreign aid - Haynes, Susan Turner, 1985- author.
1 online resource.
Keywords: "The United States contributes more foreign aid than any other state in the world, and it is often recognized as a leader in engaging religious organizations in aid delivery. Faith in Foreign Aid is the first book to closely examine how the relationship between religious organizations and USAID plays out in practice. Faith in Foreign Aid dives into twenty years of data to trace faith-based funding patterns in US foreign aid from 2001-2021. The findings show that despite America's push to engage religious organizations in aid, the total number of religious organizations it funds is relatively low, especially when compared with the number of USAID's secular partners. These FBOs also represent the minority of US-based development FBOs broadly. Deploying extensive original survey and interview data, the book investigates why this might be, and suggests that many religious organizations are deterred from applying for funding because they perceive the government as biased against them, or fear their religious mission might be challenged. Throughout the book, Faith in Foreign Aid highlights the voices and experiences of faith-based organizations, showing a way for more effective engagement between religious organizations and government actors. The book will be of interest to researchers across public policy, development, religion, and political science, as well as to practitioners at USAID and development organizations"--